Level of Evidence and Authorship Trends in Foot and Ankle Related Trauma Publications. Issue 4 (22nd October 2020) - Alexander, Bradley; Jones, James R.; Solar, Spaulding F.; Agarwal, Abhinav; Cage, Benjamin B.; Greco, Elise M.; Shah, Ashish
Category: Other Introduction/Purpose: Evidence-based research in the field of foot and ankle related trauma surgery has increased significantly over the past two decades and considerable emphasis is being put on publication quality and level of evidence (LOE). With foot and ankle surgery being a relatively new and growing field of orthopedics, minimal analysis has been performed on the LOE and authorship trends in foot and ankle related trauma publications. The purpose of this study is to evaluate LOE and authorship characteristics in foot and ankle related trauma publications in three different high impact factor journals. Methods: All of the foot and ankle related trauma publications from the years 1997, 2002, 2007, 2012, and 2017 in Foot and Ankle International (FAI), Journal of Trauma (JOT), and The Journal of Bone and Joint Surgery (American and British volumes) (JBJS) were analyzed. LOE of each article was determined by two external reviewers based on the JBJS LOE grading system. Country of origin for the first, last, and corresponding author of each article was evaluated, and fellowship data was obtained from a database for all United States authors. LOE, authorship, and publication trends were compared between both journals and publication year. Results: Over the 15-year period therapeutic studies were the prominent studies in all three journals. JBJS published the highest quality level of evidence and did not publish any level V evidence. The median number of authors was highest in JBJS. JOT publishes a majority of articles from North America (65%) while JBJS publishes more internationally (48% North American). Number of authors increased over time from a median of 3 in 1997 to a median of 5 in 2017. When evaluating the articles with available authorship fellowship data, JBJS and JOT had the highest percentage of articles with a trauma fellowship trained author at 77% and 53%, respectively. FAI had the highest percentage of articles with a foot and ankle fellowship trained author at 34%. Conclusion: From 1997 to 2017, there has been an increase in level 3 evidence foot and ankle related trauma publications and an emphasis on studies being conducted by fellowship trained authors. While the percentage of authors with MDs per publication remained similar over time, this study shows that publications have gradually increased the number of authors over time. There are key differences between the journals including level of evidence.